Conservation of Forest Genetic Resource - an ex-situ Management of Secondary Forests - Singh, U. V. (Indian Forester, 1996)
Ex-situ management for the conservation of germ plasm is one of the economic and socially accepted land use methods. Phenotypically improved germplasm for the economically valued species were selected and multiplied through vegetative reproduction. Clones of Tamarindus indica, Artocarpus integrifolia, Syzygium cumini, Santalum album, Casuarina, Eucalyptus, Feronia elephantum, Emblica officinalis and others were collected and established at Gugargatti, Dharwad. Methods of selection, management and maintenance of germ plasm are also discussed.